The comparative effects of brief or multidisciplinary intervention on return to work at 1 year in employees on sick leave due to low back pain: A randomized controlled trial. (September 2021) - Langagergaard, Vivian; Jensen, Ole Kudsk; Nielsen, Claus Vinther; Jensen, Chris; Labriola, Merete; Sørensen, Vibeke Neergaard; Pedersen, Pernille
Objective: To compare return to work (RTW) rates among patients with low back pain (LBP) and different job relations randomized to brief or multidisciplinary intervention. Design: A randomized controlled trial with 1-year follow-up. Setting: Silkeborg Regional Hospital, Denmark. Subjects: Four hundred seventy-six participants were divided into two groups concerning job relations: strong (influence on job and no fear of losing it) or weak (no influence on job and/or fear of losing it), and afterwards randomized to brief or multidisciplinary intervention. Interventions: Brief intervention included examination and advice by a rheumatologist and a physiotherapist. Multidisciplinary intervention included brief intervention plus coaching by a case manager making a plan for RTW with the patient. Main measures: Primary outcome was 1-year RTW rate. Secondary outcomes included pain intensity (LBP rating scale), disability (Roland Morris disability scale), and psychological measures (Common Mental Disorder Questionnaire, Major Depression Inventory, and EQ-5D-3L). Results: Mean (SD) age was 43.1 (9.8) years. Among 272 participants with strong job relations, RTW was achieved for 104/137 (76%) receiving brief intervention compared to 89/135 (66%) receiving multidisciplinary intervention, hazard ratio 0.73 (CI: 0.55–0.96). Corresponding results for 204 participants with weak job relations were 69/102 (68%) in both interventions, hazard ratio 1.07 (CI: 0.77–1.49). For patients with strong job relations, depressive symptoms and quality of life were more improved after brief intervention. Conclusion: Brief intervention resulted in higher RTW rates than multidisciplinary intervention for employees with strong job relations. There were no differences in RTW rates between interventions for employees with weak job relations.